Removal of Cr6+ and Pb2+ from Aqueous Solutions by Natural Zeo-Bentonite - Hashemi, Kh.; Zahiri, R.; Hashemi-Moghaddam, H. (Asian Journal of Chemistry, 2013)
In this study the ability of zeo-bentonite (zeolite-bentonite) to remove Cr(VI) and Pb(II) ions from water resources has been studied. The analysis conducted on the use zeo-bentonite shows that illite, montmorillonite and clinoptilolite are the most important minerals in the zeo-bentonites. The effect of various parameters such as initial concentration of the metal, pH solution, contact time and temperature in is considered. Results showed that, in the initial volume of 100 mL of solution and initial concentration of 0.005 mol/L, 1 g of adsorbent amount and temperature of 100 ºC, absorption of chromium 6 in pH = 5 and pH = 3 in lead 2 absorption maximum is adsorption process for both the metal is very good and very good zeo-bentonite as absorbent to absorb these metals are considered.